From Point to Sphere: Spatial Organization of Sound in Contemporary Music (after 1950) - Harley, Maria (Canadian University Music Review / Revue de musique des universités canadiennes, 1993)
In this study of spatial organization of sound, that is of "spatialization" in music, the term "spatial" refers to the three-dimensional performance space, not to pitch. "Spatialized music," distinct both from polychoral music and from musical theatre, means music with quasi-spatial structure defined by the composer in the score or in another medium of sound coding (digital or analog recording, specific software). Spatialization includes ensemble dispersion, movement of sounds, performers and audience, juxtaposition and interaction of real and virtual sound sources – every situation in which the position of the sound sources and the acoustic quality of the performance space are given compositional significance. A classification of spatial designs in music is followed by examples illustrating three aspects of spatialization: (1) the expression or simulation of geometrical patterns in music, (2) the movement of sound, (3) the symbolic function of spatial designs and movement. Musical examples and graphs of performer placement are taken from Henry Brant's Millenium II (1954), Karlheinz Stockhausen's Gruppen für drei Orchester (1955-57), Iannis Xenakis's Terrêtektorh (1965-66) and John Tavener's Ultimos Ritos (1972).